Surgical Approach in Calves with Omphalitis - Boscarato, André Giarola; Martins, William Del Conte; Pacheco, Filipe Correa; Belettini, Salviano Tramontin; Quessada, Ana Maria; Alberton, Luiz Rômulo (Acta Scientiae Veterinariae, 2021)
Background:Pathological changes in the umbilical region are common in calves. Among such alterations, omphalitis is included. This term is used to define inflammation and infection of the external structures of the umbilicus. According to the affected structures, it can be subclassified into omphalophlebitis, omphaloarteritis, omphalourachitis and panvasculitis. These inflammations are usually associated with bacterial infections. There are predisposing conditions that include inadequate handling such as poor hygiene and neglect of primary care. Omphalitis can affect the animal in a multisystemic way, compromising its well-being and bringing economic losses. In treatment, the use of antimicrobials does not always solve the problem. Thus, surgical treatment can be used, which has good results and should be the choice in the disease. The objective of this work is to report 30 cases of omphalitis in calves, submitted to surgical or conservative treatment. Materials, Methods & Results: Thirty cases of omphalitis in calves treated in the routine of the Veterinary Hospital of the Paranaense University was analyzed. On physical examination, the animals presented fever, apathy, hyporexia or anorexia and increase of umbilical volume, usually with purulent secretion. Some animals had sepsis and arthritis. In animals with sepsis, hyperemia of the episcleral vessels, dehydration and severe apathy were observed. In calves with arthritis, increased joint volume, pain on palpation and lameness were observed. In animals where the owners did not authorize the surgery, treatment was instituted with sulfadoxine and flunixim meglumine. In dehydrated calves, fluid therapy was used. Animals that were surgically treated received the same clinical treatment protocol as non-operated animals. The surgical procedure was performed under general anesthesia and consisted of resection of the affected umbilical structures. Omphalophlebitis was the most common illness. The most frequent complication was sepsis. Calves treated surgically had a higher survival rate (86.66%) than those treated clinically (46.67%). Discussion: The clinical signs presented by all animals converged with the literature, allowing for clinical diagnosis. Clinical examination is essential for diagnosis in omphalitis cases. Complementary methods include ultrasound, thermography and laparoscopy, which are important to identify changes in intra-abdominal umbilical structures. Accurate diagnosis of the involved structures was only possible in animals surgically, as well as alterations in organs such as the liver and bladder. There is great variability related to the umbilical structures involved, according to initial care, breeds, seasonality or even the method of conception. Unlike what is observed in the literature, in the present study, there was a higher prevalence of omphalophlebitis, demonstrating variability in relation to the umbilical structures involved. Sepsis, observed in 16.7% of cases, results from bacterial ascension of the umbilical structures. Lameness due to polyarthritis was found in 10% of animals. Meningoencephalitis was observed in 3.3%. Hepatic and retroperitoneal abscedation were observed in 6.7% and 3.3% of cases, respectively. Conservative treatment with antibiotics and local antiseptics has a limited effect on this type of condition, which was proven in the presentstudy, since the survival rate was statistically higher in animalssurgically treated. Keywords: surgery, umbilical structures, bovine, neonate. Descritores: cirurgia, estruturas umbilicais, bovinos, neonato. Título: Surgical Approach in Calves with Omphalitis